Tailoring the corrosion behavior of Fe-based metallic glasses through inducing Nb-triggered netlike structure. (February 2019) - Jia, C.G.; Pang, J.; Pan, S.P.; Zhang, Y.J.; Kim, K.B.; Qin, J.Y.; Wang, W.M.
Graphical abstract: Highlights: Thermodynamic parameters of Fe-based glasses hop as c Nb rises from 7 to 10 at.%. Passive ability of these glasses increases drastically as c Nb rises from 7 to 10 at.%. Netlike structure in these glasses associated with Fe23 B6 cell is verified with simulations. Netlike structure explains the structure and passivation changes in these glasses. Abstract: The atomic structure and corrosion behavior of Fe87- x B13 Nb x ( x = 0, 7, 10 and 13) metallic glasses were investigated using various experimental techniques and simulations. The netlike (Fe, Nb)23 B6 structure units, which took root in the Nb-contained amorphous matrix, emerged after annealing and raised markedly corrosion resistance of as-spun amorphous samples as c Nb > 7 at.%, such as the occurrence of wider passive platform in the potentiodynamic polarization plots and the transformation from the porous holes to stable passive films on corrosion surfaces.